A novel Solid Oxide Photoelectrolysis cell for Solar-Driven hydrogen production - Deng, Guangyu; Xu, Chenyu; Mei, Jinhao; Chen, Chen-Ge; Zhang, Yanwei (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
[Display omitted] •A novel Solid Oxide Photoelectrolysis Cell (SOPC) device was developed, enhancing SOEC performance under light illumination.•0.08Al-La0.3Sr0.7TiO3 photoresponsive electrode achieved an optimal photocurrent of 56.89 mA/cm2 and a hydrogen production rate of 10.62 mol/m2/h.•The system exhibited a high external quantum efficiency (EQE) of 30.2% and visible-light absorption at elevated temperatures.•This work bridges the gap between photocatalysis and solid oxide electrolysis, advancing sustainable hydrogen energy solutions. Solid Oxide Electrolysis Cells (SOECs) hold great potential for efficient hydrogen production through water splitting. By introducing a photoresponsive electrode into an SOEC, we developed a novel Solid Oxide Photoelectrolysis Cell (SOPC) device. This device demonstrated a substantial enhancement in SOEC performance under light illumination. Various aluminum-doped lanthanum strontium titanate (ALST) photoresponsive electrode materials were synthesized using melting methods and evaluated for their photocatalytic and electrochemical performance. Notably, ALST exhibited an optimal percentage photocurrent of 21.39 % and photocurrent of 56.89 mA/cm2, leading to a hydrogen production rate of 10.62 mol/m2/h with an external quantum efficiency (EQE) of 30.2 %. The material also showed significant visible-light absorption at elevated temperatures, enhancing its suitability for SOPCs. This study elucidates the mechanisms by which photogenerated carriers drive photocatalysis and photoelectrochemical reactions, which are crucial for optimizing SOPC performance. Ultimately, SOPC technology provides a more efficient pathway for hydrogen production, contributing to the advancement of next-generation sustainable energy solutions.